Generation of Certain Patterns Using Array-Token Petri Nets - Philomena, V. Sharon; Santhiya, R; Usha, P (International Journal of Computer Sciences and Engineering, 2025)
A Petri net is a specific type of Mathematical modeling which is useful in data analysis, simulations, business process modeling and other such scenarios. There are different types of Petri net models which models the behaviour of distributed systems. This paper presents some applications of array token Petri nets by generating certain pattern of picture languages using evolutionary rules on transitions. An Array-token Petri net (ATPN) was first defined by Beulah Immanuel by labeling tokens by arrays which generates picture languages. This paper contains two rules called elementary evolution rule (EER) and parallel evolution rule (PER) which is used to generate same pattern of picture languages in different sizes. Application of ATPN which generates English alphabetic letters treated as rectangular arrays was examined and also Petri net which generates kolam pattern was also studied. Motivated by these papers, we have generated certain patterns of picture languages using ATPNs by applying some evolution rules on transitions